Corneal elevation changes after forced eyelid closure in healthy participants and in patients with keratoconus. (18th March 2019) - Atalay, Eray; Najjar, Raymond P; Tun, Tin Aung; Özalp, Onur; Bilgeç, Mustafa D; Yıldırım, Nilgün
Abstract : Background: To assess pointwise corneal elevation changes after forced eyelid closure test (FECT) in the eyes of healthy subjects and in eyes with keratoconus. Methods: Twenty‐nine subjects with keratoconus and 31 healthy volunteers were evaluated. Patients with keratoconus who had corneal hydrops, apical scarring, corneal thickness ≤ 400 μm, ocular surface disease, contact lens wear on the examination day and a history of corneal cross‐linking were excluded. Exclusion criteria for healthy participants were spherical error > +3.00 D and < −3.00 D, corneal astigmatism > 1.50 D, corneal curvature > 47 D, ocular allergy, clinical findings and family history of keratoconus. Pentacam was performed before and after 20 seconds of FECT and raw data were extracted from the built‐in software. Pointwise anterior and posterior elevation changes in the central 8 mm cornea were assessed using paired samples t‐test and heat maps were constructed to reflect mean changes and statistically significant data points. Statistical significance was assumed at p < 0.01. Results: Age and gender were similar between healthy subjects (24.5 ± 1.6 years, 46.4 per cent female) and subjects with keratoconus (28.6 ± 9.2 years, 46.4 per cent female, p = 0.19, 0.61, respectively). Healthy eyes displayed posterior depression clustering in the inferotemporal and inferonasal areas (mean change: −4.5 ± 7.8 μm and −5.2 ± 9.8 μm, respectively, all p < 0.01). In contrast, keratoconus eyes exhibited a wider area of posterior elevation clustering in the inferior cornea (mean change: 8.1 ± 14.5 μm, all p < 0.01) with a small extension in the inferotemporal cornea (mean change: 12.1 ± 22.3 μm, all p < 0.01). Conclusion: FECT elicits corneal elevation changes mainly in the inferior cornea with the change being more pronounced and wider in eyes with keratoconus.